Programmable mechanical metamaterials: basic concepts, types, construction strategies—a review - Liu, Chenyang; Zhang, Xi; Chang, Jiahui; Lyu, You; Zhao, Jianan; Qiu, Song (Frontiers in Materials, 2024)
Metamaterials have been a hot topic over the past two decades, involving scientific research directions in materials, engineering, and physics. Among them, programmable mechanical metamaterials are an emerging class of metamaterials that offer intelligent programming and control of diverse mechanical properties, such as stiffness, damping, thermal expansion, and shape memory behavior. Meanwhile, it can be rationally designed to have specific geometric architectures and programming strategies in response to different types of external stimuli, such as temperature, electric and magnetic fields, and mechanical loads. These intelligent mechanical properties have a wide range of potential applications due to their uniqueness and controllability, including soft robotics, adaptive structures, and wearable devices. Thus, the programming strategies to achieve them are particularly critical. Combined with related programmable thinking concepts, this paper briefly reviews programming strategies for programmable mechanical metamaterials, including geometric, structural, and external driving force programming. Meanwhile, this paper presents the principles of programming strategies classified according to different programmable mechanical properties (e.g., programmable stiffness, deformation, multistability) and looks ahead to the challenges and opportunities for future research.